Payments System Modernization: Opportunities & Challenges for the Business (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The effective project in a new payment systems forms modifies and improves it for the business. A payment system can have different stages of its formation which depends on company situation. But it is permanent in its essence. The research forms the phase of a new (modernized) payment system. Each step such as preparation phase, project phase, testing, and implementation) has its special meaning. In the preparatory phase, a project team determines the directions of the payment system strategy, defines the goals of the organization and its departments. After that, a project team analyzes objective and subjective factors of the payment system, to answer the question whether it meets the company objectives and improve the strategy enterprise development for the business. The project phase begins with accumulation the experience of previous stages. After that, a process determines the frames of the subjective items, to answers the question whenever it demands full or partial changes. It identifies the components of the remuneration and their proportionality, payment methods, principles of its formation, commercial sources. The testing of the payment system can include different methods, which depends on the company circumstances. Consultations are the first form in the stage which include pieces of advice of the chiefs in the various levels of management, who represent different departments. Furthermore, it is essential to adopt approaches to the different departments and groups of employees. We can reach it with the selection of a random company staff from each department. The company should promote the payment system, do marketing research, convince stakeholders and company's employees in its implementation, like it do it for other companies innovation. Positive perception of the system is the half of the success in its implementation. Managers should inform employees about changes in the payment system. That will enhance the understanding of the new or modified system. On the other hand, the company needs to define the time of its implantation, because it can hurt other plans and projects.
Keywords: the stages of the payment system formation, planning process, remuneration system, objective and subjective analyze of a payment system